Radiation and nuclear techniques in material science Selected, peer reviewed papers from the Conference on Physical-Technical Problems of Nuclear Science, Energy Generation and Power Industry (PTPAI-2014), June 5-7, 2014, Tomsk, Russia - Dolmatov, Oleg Y.; Stepanov, Igor B.; Liventsov, Sergey N. (Advanced materials research ;, 2015)
Collection of selected, peer reviewed papers from the Conference on Physical-Technical Problems of Nuclear Science, Energy Generation and Power Industry, (PTPAI-2014), June 5-7, 2014, Tomsk, Russia. The 151 papers are grouped as follows: Chapter 1: Materials Science and Technologies;Chapter 2: Plasma, Microwave, Ion, Electron and Isotope Technologies; Chapter 3: Nuclear Engineering and Fuel Cycles;Chapter 4: Radiation Technologies in Medicine;Chapter 5: Computation, Automation, Information Technologies and Safety Systems in Nuclear Industry Keyword: Nuclear technologies, nuclear science, radiation techniques, materials science, surface science, physical chemistry, condensed state physics, information technologies, automation systems, radioactive materials research, plasma production, plasma properties, isotopes obtaining, nuclear medicine, numerical approaches, simulation processes, atomic power industry 2014 was the 60th anniversary of the Department of Electronics and Automation of Nuclear Plants. To celebrate this anniversary the National Research Tomsk Polytechnic University in Tomsk, Russia dedicated the VIth International Conference "Physical-Technical Problems of Nuclear Science, Energy Generation and Power Industry" to allowing scientists and industrial specialists in the field of Atomic Power to discuss the state of the field. This book contains the proceedings from that conference. Major topics discussed include materials science and technology; plasma, microwave, ion, electron and isotope technologies; nuclear engineering and fuel cycles; radiation technologies in medicine; and computation, automation, information technologies and safety systems in the nuclear industry. -- Energy engineering-- Materials science-- Nuclear engineering.